Accounting for sustainability / edited by Gunnar Rimmel. - Rimmel, Gunnar (Routledge, 2026)
This edited volume provides a broad overview of how sustainability reporting has grown, how it is used now and where it is heading. Daily, we read and hear in various media about concepts such as corporate social responsibility (CSR), sustainability reporting, sustainability accounting, environmental reports, corporate citizenship or environmental management systems.